2020
DOI: 10.21315/mjms2020.27.4.15
|View full text |Cite
|
Sign up to set email alerts
|

Ivermectin: Potential Role as Repurposed Drug for COVID-19

Abstract: Severe acute respiratory illness caused by 2019 novel coronavirus (2019-nCoV), officially named severe acute respiratory syndrome coronavirus (SARS-CoV-2) in late December 2019 is an extremely communicable disease. World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) as a pandemic as it has spread to at least 200 countries in a short span of time. Being a new disease there is lack of information about pathogenesis and proliferation pathways of this new coronavirus. Currently there is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Ivermectin is a semisynthetic anthelmintic agent that selectively binds to glutamate-gated chloride ion channels found in nerve and muscle cells of invertebrates (3). However, an antiviral activity in RNA and DNA viruses has also been reported (4).…”
Section: Introductionmentioning
confidence: 99%
“…Ivermectin is a semisynthetic anthelmintic agent that selectively binds to glutamate-gated chloride ion channels found in nerve and muscle cells of invertebrates (3). However, an antiviral activity in RNA and DNA viruses has also been reported (4).…”
Section: Introductionmentioning
confidence: 99%
“…The antiviral activity of IVM had been reported previously, wherein IVM was found to have in-vitro activity against both RNA and DNA viruses including human immunodeficiency virus type 1, influenza virus, Venezuelan equine encephalitis virus, dengue virus, yellow fever virus and Zika virus [ 7 , 8 ]. In April 2020, the in-vitro activity of IVM against SARS-CoV-2 was reported: a single dose of the drug administered after 2 h of infecting cultured Vero/hSLAM cells reduced the viral load up to 5000 times within 48 h [ 9 ].…”
Section: Introductionmentioning
confidence: 88%
“…A single dose of IVM effectively removed SARS-CoV-2 viral RNA in cell culture by 48 h. It was suggested that IVM might be used for the treatment of COVID-19 patients in the early phase with mild to moderate symptoms, PCR positive for SARS-CoV-2 virus, and those without comorbidities such as chronic obstructive pulmonary disease, diabetes, hypertension, obesity, acute or chronic renal failure, and coronary diseases. IVM suggested anti-CoV-2 effects are based on in vitro studies, showing that this compound inhibits the importin alpha/beta-1 nuclear transporter, and thus, in cell cultures, reduces the replication of various viruses including SARS-CoV-2 (Bray et al 2020 ; Caly et al 2020 ; Rizzo 2020 ; Sharun et al 2020 ; Heidary and Gharebaghi 2020 ; Dixit et al 2020 ; Chaccour et al 2020a , b ; Formiga et al 2020 ). In addition, in a silico-based analysis of Ivermectin’s molecular interaction indicates positive interaction of Ivermectin with viral protein targets, which is leading for SARS-CoV 2 N-protein NTD (nucleocapsid protein N-terminal domain) (Kaur et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%